Regional anesthesia training model for resource-limited settings: a prospective single-center observational study with pre–post evaluations. Issue 7 (July 2020) - Brouillette, Mark A; Aidoo, Alfred J; Hondras, Maria A; Boateng, Nana A; Antwi-Kusi, Akwasi; Addison, William; Singh, Sanjeev; Laughlin, Patrick T; Johnson, Benjamin; Pakala, Swetha R
Abstract : Background and objectives: Educational initiatives are a sustainable means to address provider shortages in resource-limited settings (RLS), yet few regional anesthesia curricula for RLS have been described. We sought to design a reproducible training model for RLS called Global Regional Anesthesia Curricular Engagement (GRACE), implement GRACE at an RLS hospital in Ghana, and measure training and practice-based outcomes associated with GRACE implementation. Methods: Fourteen of 15 physician anesthesiologists from the study location and three from an outside orthopedic specialty hospital consented to be trainees and trainers, respectively, for this prospective single-center observational study with pre–post evaluations. We conducted an initial needs assessment to determine current clinical practices, participants' learning preferences, and available resources. Needs assessment findings, expert panel recommendations, and investigator consensus were then used to generate a site-specific curriculum that was implemented during two 3-week periods. We evaluated trainee satisfaction and changes in knowledge, clinical skill, and peripheral nerve block (PNB) utilization using the Kirkpatrick method. Results: The curriculum consisted of didactic lectures, simulations, and clinical instruction to teach ultrasound-guided PNB for limb injuries. Pre–post evaluations showed trainees were satisfied with GRACE, median knowledge examination score improved from 62.5% (15/24) to 91.7% (22/24) (p<0.001), clinical examination pass rate increased from 28.6% (4/14) to 85.7% (12/14) (p<0.01), and total PNB performed in 3 months grew from 48 to 118. Conclusions: GRACE applied in an RLS hospital led to the design, implementation, and measurement of a regional anesthesia curriculum tailored to institutional specifications that was associated with positive Kirkpatrick outcomes.